Recent Advances in Optical DNA Biosensors Technology - Bambang Kuswandi; Sara Tombelli; Giovanna Marazza; Marco Mascini (CHIMIA, 2005)
Recent advances in nucleic acids-based biosensors have led to the development of DNA biosensors for DNA hybridisation detection and for nucleic acid–ligand binding studies. This review presents a concise description and an evaluation of the optical devices that have been employed in the development of optical DNA biosensors. Such optical devices include optical fibres, planar waveguide, surface plasmon resonance, resonant mirror and surface-enhanced Raman scattering. The specificity and response of each optical DNA biosensor are discussed. Overall, a rapid growth in the development of optical DNA biosensor technology will be seen in the near future, which will lead to the establishment of optical DNA biosensor technology as a major tool of analytical biochemistry.